Outcome of Dynamic Condylar Screw with Plate versus Distal Femoral Lock Compression Plate Fixation in Fracture of Distal Femur (Medicine Today, 2021)
Introduction: The dynamic compression screw with plate implant used to treat fractures of the distal femur. The distal femoral lock compression plate fixation is designed as an alternative surgical option to treat these fractures. The objective of this study was to assess the comparative endurance of both devices. The objective of the study is to compare the outcome of DF-LCP and DCS fixation in distal femoral fractures.Materials and Methods: This prospective comparative study was conducted in the Department of Orthopaedics, Sylhet MAG Osmani Medical College Hospital, Sylhet between January 2011 and December 2012. Thirty patients with AO type 33-B and 33-C fracture were selected and were divided randomly into group-A and group-B by odd and even number. Dynamic condylar screw (DCS) fixation was used in group-A and distal femoral locking compression plate (DF-LCP) fixation in group-B.Results: DCS group [9 male, 6 female; mean age, 44.9 ± 12.9 years] and DF-LCP group [10 male, 5 female; mean age, 42.6 ± 15.7) years] were similar in age (p=0.660) and sex (p=0.705). The total operation (minutes) [92.3 ± 7.5 versus 90.4 ± 6.9; p=0.484], length of postoperative hospital stay (days) [6.0 ± 0.9 versus 5.9 ± 0.9; p=0.695] and union time (weeks) [20.6 ± 5.0 versus 18.7 ±3.3 weeks; p=0.238] did not differ significantly between two groups. Total complications [6 (40.0%) versus 4 (26.7%); p=0.439] was also similar in both groups. Functional outcome was excellent in 13.3%, good in 33.3%, fair in 33.3% and poor in 20.0% cases in DCS group; while excellent in 53.3%, good in 20.0% fair in 6.7% and poor in 20.0% of cases in DF-LCP group; different was not significant (p=0.080).Conclusion: Dynamic condylar screw with plate and distal femoral locking compression plate fixation are equally effective for achieving satisfactory union and functional outcome in AO type 33-B, 33-C fracture distal femur.Medicine Today 2021 Vol.33(1): 45-49